Endodermal sinus tumor of testis with acute intestinal obstruction: A rare presentation - Mukhopadhyay, Biswanath (Medknow Publications & Media Pvt Ltd, 2012)
A 7-year-old boy reported with endodermal sinus tumor of left testis, jejunal metastasis and intestinal obstruction. He was treated by high inguinal orchidectomy and resection of jejunal mass followed by chemotherapy.